Self-Identification and Repositioning of the Tengananese in the Discourse of Adat Community in Bali - Suyadnya, I Wayan (UI Scholars Hub, 2019)
Along with the Hindu religion and culture, adat is recognized as a strong characteristic to describe the level of kebalian (Baliness). Adat appears as a control for the emergence of social, religious, and cultural problems. In practice, it also shows a strong dominance to discipline members of community to adhere to state regulations. However, the discourse on adat also provides an illustration of how adat can be used as a differentiating strategy in everyday customary practices. In performing an ethnographic study in Tenganan Pegringsingan, a community that in colonial literature is referred as “Bali Aga”, this article investigates how adat is shaped and deployed by various actors to define their identity and reposition themselves in the dominant discourse of southern Bali. This article challenges the general assumption that after the Reforms, the adat revival movement was carried out to achieve recognition and receive protection from the state. This article instead shows that the adat movement in Bali tends to diverge from the global indigenous movement. The movement that was constructed does not correlate with the global indigenous movement. The article argues that the Tenganan people only used self-identification strategies to emphasize the differences in the position of their group in Bali.